"Setting people up for success and then failure" - health care and service providers' experiences of using prize-based contingency management - Marilou Gagnon; Adrian Guta; Alayna Payne (BMC, 2020)
Abstract Background Over the last 50 years, there has been a growing interest in and use of contingency management (CM) for people who use substances. Yet, despite showing some level of efficacy (albeit only short-term) and being praised by researchers as beneficial and cost-saving, it continues to be underutilized by health care and service providers. Why that is remains unclear. Methods Recognizing a gap, we conducted a targeted analysis of a larger set of qualitative interviews conducted on the experience of health care and service providers with incentives (including prize-based CM) (n = 25). Results Four themes were identified during the analysis: 1) The specificities of prize-based CM, 2) The role of providers in administering prize-based CM, 3) The positive and negative impact on the relationship, and 4) The ethical concerns arising from prize-based CM. Overall, our findings are consistent with existing literature and suggest that providers are wary of using prize-based CM because they tend to value effort over success, support over reward, honesty over deceit, and certainty over probability and variability. Conclusion Our analysis offers additional insights into the experiences of providers who use prize-based CM and possibly some indications as to why they may not wish to work with this type of incentive. The question raised here is not whether there is enough evidence on the effectiveness of prize-based CM, but rather if this type of incentive is appropriate and ethical when caring for people who use substances.